2011
DOI: 10.7202/045779ar
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrated pork manure by-product: effect of a chitosan amendment on bacterial community and common scab incidence

Abstract: Chitosan amendment modified the composition of a microbial community associated with dehydrated pork manure by-product. The amended product (biosolid PC) contained a lower number of anaerobic bacteria than the non-amended product (biosolid P). Chitosan also significantly reduced the fungal population. A 16S rRNA gene bank constructed from DNA extracted from the bacterial community associated with both P and PC biosolids revealed that bacterial ordersXanthomonodales, Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…This decrease could be correlated to the healthier condition observed in the treated plants compared to the control plants. Several studies have also reported that chitosan and chitinous soil amendment, contribute to plant protection by modifying the microbial community and stimulating plant defense mechanisms (Benhamou et al, 1994;Roy et al, 2010). Furthermore, Xing et al (2013) showed that nontreated and heat-treated oyster shell powder exhibited antifungal activities.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This decrease could be correlated to the healthier condition observed in the treated plants compared to the control plants. Several studies have also reported that chitosan and chitinous soil amendment, contribute to plant protection by modifying the microbial community and stimulating plant defense mechanisms (Benhamou et al, 1994;Roy et al, 2010). Furthermore, Xing et al (2013) showed that nontreated and heat-treated oyster shell powder exhibited antifungal activities.…”
Section: Discussionmentioning
confidence: 97%
“…The positive charge of chitosan confers to it numerous and unique physiological and biological properties with great potential in a wide range of agricultural practices (Bautista-Banos et al, 2004;Tang et al, 2010). Many studies have reported the capacity of chitosan to stimulate the immune system for plant resistance to pathogen infection, to induce the accumulation of phytoalexins resulting in antifungal responses in order to enhance protection against further infection (Coqueiro et al, 2011) and also to change the soil microorganisms content (Roy et al, 2010). Moreover, chitosan has been widely used as a growth stimulator, germination accelerator and yield enhancer in many crop species such as in orchid (Uthairatanakij et al, 2007), faba bean (El-Sawy et al, 2010), cucumber (Shehata et al, 2012) and corn (Boonlertnirun et al, 2011;Lizárraga-Paulín et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This decrease of leaf disease symptoms could be correlated to the higher levels of resistance which might be due to the stimulation of cocoa seedling defense mechanisms by heat-treat oyster shell powder component such as chitin and calcium. [12] and [31] argued that organic chitinous amendment exhibited antifungal activities and stimulated plant defense mechanisms. Results from these studies suggested that the mechanism of disease suppression could be the induction of systemic resistance since there was no direct contact between P. megakarya and oyster shell powder within the plant.…”
Section: Discussionmentioning
confidence: 99%